Paralomis makarovi Hall & Thatje, 2009, n. sp. ... - Hall, Sally; Thatje, Sven (Zenodo, 2009)
Paralomis makarovi n. sp. (Figs 3, 4) Material examined. Bering Sea: Bowers Bank, 54°30’N, 179°17’E, Albatross station 4772, 4.06. 1906, 629 m: male holotype, CL 23.8 mm; 3 male paratypes, CL 15–25 mm; 3 female paratypes. CL 12–23 mm (all USNM 1122582). Etymology. This new species is named after V.V. Makarov, the author of an influential 1938 monograph on lithodid biogeography. Description of the holotype. Carapace pear-shaped; rounded posteriorly, and longer than wide. Dorsal surface covered uniformly by conical spines, each with band of long setae half-way along length (Fig. 4 c) No spines dorsally or laterally notably longer than any other — no prominent spine at apex of gastric or branchial regions. Gastric region rounded and more prominent than branchial and cardiac regions, which are relatively sunken. Grooves only partially delimiting regions. Median spine of rostrum strongly curved upward, and without secondary spinules or tubercles on ventral surface; one pair of dorsal spines, and one pair of ... : Published as part of Hall, Sally & Thatje, Sven, 2009, Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution, pp. 31-47 in Zootaxa 2302 on pages 36-39, DOI: 10.5281/zenodo.191756 ...